2019
DOI: 10.1002/jmri.26728
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of MRI compared with CT for the etiology of abdominal pain in emergency department patients with concern for appendicitis

Abstract: Background Computed tomography (CT) is commonly used in the Emergency Department (ED) to evaluate patients with abdominal pain, but exposes them to ionizing radiation, a possible carcinogen. MRI does not utilize ionizing radiation and may be an alternative. Purpose To compare the sensitivity of MRI and CT for acute abdominopelvic ED diagnoses. Study Type Prospective, observational cohort. Population ED patients ≥12 years old and undergoing CT for possible appendicitis. Field Strength/Sequence 1.5 T MRI, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Eight primary cohort studies were identified that compared MRI and the reference standard with respect to their ability to identify alternative diagnoses when appendicitis was clinically suspected. 31 , 34 , 39 , 42 , 43 , 46 , 62 , 63 The sensitivity and specificity of MRI for alternative diagnoses ranged between 77.0–100% 34 , 62 and 94.9–100%, 34 , 43 respectively. Seven of these studies additionally reported the data with a restriction to gynaecological pathologies, with the values of sensitivity and specificity ranging between 57.1–100% 34 , 63 and 95.3–100%, 34 , 43 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight primary cohort studies were identified that compared MRI and the reference standard with respect to their ability to identify alternative diagnoses when appendicitis was clinically suspected. 31 , 34 , 39 , 42 , 43 , 46 , 62 , 63 The sensitivity and specificity of MRI for alternative diagnoses ranged between 77.0–100% 34 , 62 and 94.9–100%, 34 , 43 respectively. Seven of these studies additionally reported the data with a restriction to gynaecological pathologies, with the values of sensitivity and specificity ranging between 57.1–100% 34 , 63 and 95.3–100%, 34 , 43 respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 67 The variable results on the sensitivity of MRI may be partially attributable to the varying levels of MRI experience of the interpreting radiologists in different studies, 34 , 63 as the sensitivity of MRI interpretation can improve with training. 62 …”
Section: Discussionmentioning
confidence: 99%
“…As popularized imaging tools for acute appendicitis, the sensitivity and speci city were reported to be over 90% for CT and over 80% for ultrasound [9,10]. The sensitivity of noncontrast-enhanced MRI can also approach 77% [11]. With technological innovations, researchers or clinicians start to pay more attention in timely and accurately identifying pathological types of appendicitis before treatment.…”
Section: Introductionmentioning
confidence: 99%